2014
DOI: 10.1155/2014/501043
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Obstruction Following Computed Tomography and Magnetic Resonance Enterography Using Psyllium Seed Husk As an Oral Contrast Agent

Abstract: The authors report a case series describing four patients who developed small bowel obstruction following the use of psyllium seed husk as an oral contrast agent for computed tomography or magnetic resonance enterography. Radiologists who oversee computed tomography and magnetic resonance enterography should be aware of this potential complication when using psyllium seed husk and other bulking agents, particularly when imaging patients with known or suspected small bowel strictures or active inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…The use of this high dose of psyllium may carry the risk of bowel obstruction in patients with pre-existing small bowel strictures. 30 This is demonstrated by two cases of obstruction in a combined cohort of 68 patients with Crohn's disease undergoing CTE with psyllium. 24,25,30 More studies are required before the risk of obstruction in MRE can be established.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The use of this high dose of psyllium may carry the risk of bowel obstruction in patients with pre-existing small bowel strictures. 30 This is demonstrated by two cases of obstruction in a combined cohort of 68 patients with Crohn's disease undergoing CTE with psyllium. 24,25,30 More studies are required before the risk of obstruction in MRE can be established.…”
Section: Discussionmentioning
confidence: 97%
“…30 This is demonstrated by two cases of obstruction in a combined cohort of 68 patients with Crohn's disease undergoing CTE with psyllium. 24,25,30 More studies are required before the risk of obstruction in MRE can be established. Nonetheless, there have been no cases of small bowel obstruction using sorbitol, and it is able to provide the same degree of distension.…”
Section: Discussionmentioning
confidence: 97%
“…This was mainly due to the fact that, Psyllium is inexpensive, easy to prepare, and well-tolerated by the patients. Chen et al [ 20 ] presented four cases who developed a small bowel obstruction following the usage of Psyllium as an oral contrast in CTE and MRE. Only one of them needed operative intervention while the other three were treated conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of them needed operative intervention while the other three were treated conservatively. The authors concluded that, the presence of small bowel strictures is a risk factor for obstruction following the usage of Psyllium in the oral contrast [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although deaths due to poppy seed ingestion have not been reported, complications resulting from ingestion of other seed types, such as pumpkin, sunflower, psyllium seed husk (a bulk forming laxative), and sesame seeds, have been described. In many of these cases, individuals had a history of bowel stricture or narrowing, low water intake and older age . Symptoms ranged from abdominal pain and vomiting to peritonitis with ischemic bowel changes requiring surgical intervention.…”
Section: Discussionmentioning
confidence: 99%